Applying research in nutrition education planning: a dietary intervention for Bangladeshi chronic kidney disease patients. Issue 4 (13th December 2012) - de Brito‐Ashurst, I.; Perry, L.; Sanders, T. A. B.; Thomas, J. E.; Dobbie, H.; Yaqoob, M. M.
Abstract: Background: Effective nutrition health interventions are theory‐based, as well as being drawn from practice and research, aiming to successfully accomplish dietary behavioural changes. However, the integration of theory, research and practice to develop community dietary educational programmes is a challenge that many interventionists feel ill equipped to achieve. Methods: In the present study, a community‐based education programme was designed for Bangladeshi patients with chronic kidney disease and hypertension. The goal of this programme was to reduce dietary salt intake in this population group, with a view to reducing their blood pressure and slowing kidney disease progression. Results: The present study sets out the first four steps of a six‐step model for creating a behaviour change programme. Conclusions: These four steps were concerned with the translation of theory and evidence into intervention objectives, and illustrate how a practical, community‐based intervention was developed from behavioural theory, relevant research, knowledge of practice and the target patient group. Steps 5 and 6, which are concerned with implementation and evaluation, will be reported separately.